Factors affecting self-perceived mental health in the general older population during the COVID-19 pandemic: a cross-sectional study - Koppner, Jenny; Lindelöf, Ann; Iredahl, Fredrik; Tevell, Maxine; Nilsson, Staffan; Thorsell, Annika; Faresjö, Åshild; Israelsson Larsen, Hanna (BMC public health, 2024)
Mental health problems among older people are large public health concerns but often go unrecognized and undertreated. During COVID - 19 several restrictions regarding social contacts were launched, primarily for the old. The objective of this study is to investigate which factors that had the main negative affect on mental health in the older population during the pandemic. A cross-sectional cohort study set in Swedish primary care during the pandemic years 2021-2022. The population constitutes of 70-80-years-old, N = 260. Instruments used are Geriatric depression scale 20 (GDS20); Hospital anxiety and depression scale (HADS), and Perceived stress scale 10 (PSS10). Sociodemography and risk factors are explored. Outcome measures are factors independently associated with decreased mental health. Analyses were performed for the group as a whole and with logistic regression models comparing individuals who stated they were mentally affected by the pandemic to individuals who stated they were not. Participants who stated they were mentally affected by the COVID - 19 pandemic reported significantly higher levels of anxiety (p < 0.001), depression (p < 0.001), and stress (p = 0.026) compared to those who stated they were not mentally affected. Explanatory regression models of up to 50% showed that following factors were prominent among individuals who reported a decline in their mental health due to the COVID - 19 pandemic (n = 24); impaired social life (OR 20.29, p < 0.001, CI 4.53-90.81), change in physical activity (OR 5.28, p = 0.01, CI 1.49-18.72), perceived family situation (OR 31.90, p = 0,007, CI 2,53-402.42), mild/moderate and high anxiety (OR 4.94, p = 0.034, CI 1.13-21.60, OR 7.96, p = 0.035, CI 1.16-54.53 respectively), and female gender (OR 6.52, p = 0.029, CI 1.22-34.92). Anxiety, family situation, social life and change in physical activity were the main factors influencing the 70-80-years-old's self-perceived mental health during the COVID - 19 pandemic. Long-term effects of social restrictions on mental health in the older population need to be further investigated.